Step * 1 1 of Lemma satisfies-negate-poly-constraint

.....assertion..... 
1. eqs iPolynomial() List
2. ineqs iPolynomial() List
3. : ℤ ⟶ ℤ
⊢ ¬satisfies-poly-constraints(f;<eqs, ineqs>)
⇐⇒ (∃e∈eqs. (0 ≤ int_term_value(f;ipolynomial-term(minus-poly(add-ipoly(e;const-poly(1))))))
    ∨ (0 ≤ int_term_value(f;ipolynomial-term(add-ipoly(e;const-poly(-1))))))
    ∨ (∃ineq∈ineqs. 0 ≤ int_term_value(f;ipolynomial-term(minus-poly(add-ipoly(ineq;const-poly(1))))))
BY
RepUR ``satisfies-poly-constraints`` }

1
1. eqs iPolynomial() List
2. ineqs iPolynomial() List
3. : ℤ ⟶ ℤ
⊢ ¬((∀p∈eqs.int_term_value(f;ipolynomial-term(p)) 0 ∈ ℤ) ∧ (∀p∈ineqs.0 ≤ int_term_value(f;ipolynomial-term(p))))
⇐⇒ (∃e∈eqs. (0 ≤ int_term_value(f;ipolynomial-term(minus-poly(add-ipoly(e;const-poly(1))))))
    ∨ (0 ≤ int_term_value(f;ipolynomial-term(add-ipoly(e;const-poly(-1))))))
    ∨ (∃ineq∈ineqs. 0 ≤ int_term_value(f;ipolynomial-term(minus-poly(add-ipoly(ineq;const-poly(1))))))


Latex:


Latex:
.....assertion..... 
1.  eqs  :  iPolynomial()  List
2.  ineqs  :  iPolynomial()  List
3.  f  :  \mBbbZ{}  {}\mrightarrow{}  \mBbbZ{}
\mvdash{}  \mneg{}satisfies-poly-constraints(f;<eqs,  ineqs>)
\mLeftarrow{}{}\mRightarrow{}  (\mexists{}e\mmember{}eqs.  (0  \mleq{}  int\_term\_value(f;ipolynomial-term(minus-poly(add-ipoly(e;const-poly(1))))))
        \mvee{}  (0  \mleq{}  int\_term\_value(f;ipolynomial-term(add-ipoly(e;const-poly(-1))))))
        \mvee{}  (\mexists{}ineq\mmember{}ineqs.  0 
                                        \mleq{}  int\_term\_value(f;ipolynomial-term(minus-poly(add-ipoly(ineq;const-poly(1))))))


By


Latex:
RepUR  ``satisfies-poly-constraints``  0




Home Index